Effects of Educational Interventions on Human Papillomavirus Vaccine Acceptability: A Randomized Controlled Trial. Issue 2 (August 2019) - Cory, Lori; Cha, Beda; Ellenberg, Susan; Bogner, Hillary R.; Hwang, Wei-Ting; Smith, Jennifer S.; Haggerty, Ashley; Morgan, Mark; Burger, Robert; Chu, Christina; Ko, Emily M.
Abstract : OBJECTIVE: To estimate whether targeted educational interventions can increase human papillomavirus (HPV) vaccine acceptability and knowledge among young women. METHODS: An exploratory phase of the study was conducted to determine baseline acceptance of the prophylactic HPV vaccine and barriers to acceptance. Based on the results of that phase of the study, a randomized controlled trial of women aged 12–26 at a single institution was completed. A sample size of at least 84 women in each of three study arms (control, educational handout, or educational video) was planned to detect a 20% difference in vaccine acceptability among arms. All participants completed a survey collecting data on demographics, HPV vaccine preferences, and HPV vaccine knowledge after completion of their randomization assignments. The primary outcome was HPV vaccine acceptability. The secondary outcome was HPV vaccine knowledge. RESULTS: From March 2017 through August 2017, 256 women were randomized to one of three study arms: control (n=85), educational handout (n=84), or educational video (n=87). Demographics were similar between study arms. Overall, 51.7% of participants in the educational video arm reported willingness to accept the HPV vaccine compared with 33.3% and 28.2% of participants in the educational handout and control arms, respectively ( P <.01). Those in the educational video and handout arms had higher median HPV vaccine knowledge scores than those in the control arm (6 and 5 vs 3, P <.01). Both interventions were reported as helpful in learning (97.7% vs 92.9%, P =.15), but the educational video arm was more likely to be helpful in deciding on vaccination (86.2% vs 70.2%, P <.01). CONCLUSION: Targeted educational interventions increase HPV vaccine acceptability and knowledge among young women. Follow up studies are needed to determine whether these interventions also increase rates of vaccine uptake and series completion. CLINICAL TRIAL REGISTRATION: Clinicaltrials.gov, NCT03337269. Abstract : Targeted educational interventions increase human papillomavirus vaccine acceptability and knowledge among young women.